Molecular analysis of pathogenic Escherichia coli isolated from cow meat in Yogyakarta, Indonesia using 16S rRNA gene (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Indraswari A, Suardana IW, Haryanto A, Widiasih DA. 2021. Molecular analysis of pathogenic Escherichia coli isolated from cow meat in Yogyakarta, Indonesia using 16S rRNA gene. Biodiversitas 22: 4566-4573. Meat has been recognized as a major source of foodborne disease and a public health problem. The characteristics of meat become an ideal growth medium for various microorganisms if not handled properly. Pathogenic Escherichia coli is one of the foodborne disease agents that causes diarrhea. Identification of pathogenic E. coli isolated from cow meat needs to be done. This research aims to study nucleotide sequence of 16S rRNA gene of pathogenic E. coli isolated from cow meat in Yogyakarta, Indonesia using Polymerase Chain Reaction (PCR). These fifteen isolates have been detected for eae target gene, then amplification of the 16S rRNA gene was carried out using primers 27F and 1492R. Phylogenetic tree reconstruction was performed on the fifteen isolates of pathogenic E. coli to figure out the relationship to reference strains available at the GenBank. Results show that nucleotide sequence among the fifteen isolates from different traditional markets in Yogyakarta, Indonesia and reference strains are very similar. The fifteen isolates have small genetic distance to the reference strains, and these fifteen isolates are also in the same clade with reference strains. This research shows that the fifteen isolates under investigation are closely related to the reference strains, which is Shiga-toxin producing E. coli (STEC). People should pay more attention in processing food stock, especially cow meat. Further research may focus on determining the strain of those fifteen isolates.
Keywords: 16S rRNA; cow meat; pathogenic E. coli; phylogenetic; sequencing DNA